A Study on Trans-para-Sasakian Manifolds - Irem KUPELI ERKEN; Mustafa OZKAN (Journal of Innovative Science and Engineering)
In the current paper, we make the first contribution to investigate conditions under which three-dimensional trans-para-Sasakian manifold has η-parallel Ricci tensor and cyclic parallel Ricci tensor. Finally, a three dimensional trans-para-Sasakian manifold example which satisfies our results is constructed